FISH FARMERS’ TERMS OF TRADE (FTT) IN BREAKWATER BASED POLYCULTURE SYSTEMS IN BABULU LAUT VILLAGE, INDONESIA - Adi Hussein Nugroho; Fitriyana Fitriyana; Juliani Juliani; Said Abdusysyahid; Heru Susilo (Universitas Mataram, 2026)
This study analyzed the Fish Farmers’ Terms of Trade (FTT) of tiger shrimp (Penaeus monodon) and milkfish (Chanos chanos) polyculture farmers in Babulu Laut. Data were collected through observation, interviews, and questionnaires from nine purposively selected farmers. The average annual income from aquaculture reached IDR 1,864,014,889 per farmer. Meanwhile, the average annual aquaculture production cost was IDR 470,447,421, and household consumption expenditure was IDR 134,006,667, resulting in a total annual household expenditure of IDR 604,454,088. The calculated household FTT value was 308, indicating that farmers’ income was 3.08 times higher than their total household expenditure. In addition, the aquaculture business FTT reached 396, showing strong profitability at the production level. These findings demonstrate solid economic performance and favorable household welfare among polyculture farmers. The diversification of commodities, supported by high market prices of tiger shrimp and stable milkfish production, contributes to income stability and strengthens the role of coastal aquaculture as the primary economic support for farming households. Further development through post-harvest value addition is recommended to enhance income sustainability.